Spectral Arctic A History of Dreams and Ghosts in Polar Exploration (University College London, 2018)
Visitors to the Arctic enter places that have been traditionally imagined as otherworldly. This strangeness fascinated audiences in nineteenth-century Britain when the idea of the heroic explorer voyaging through unmapped zones reached its zenith. The Spectral Arctic re-thinks our understanding of Arctic exploration by paying attention to the importance of dreams and ghosts in the quest for the Northwest Passage. The narratives of Arctic exploration that we are all familiar with today are just the tip of the iceberg: they disguise a great mass of mysterious and dimly lit stories beneath the surface. In contrast to oft-told tales of heroism and disaster, this book reveals the hidden stories of dreaming and haunted explorers, of frozen mummies, of rescue balloons, visits to Inuit shamans, and of the entranced female clairvoyants who travelled to the Arctic in search of John Franklin's lost expedition. Through new readings of archival documents, exploration narratives, and fictional texts, these spectral stories reflect the complex ways that men and women actually thought about the far North in the past. This revisionist historical account allows us to make sense of current cultural and political concerns in the Canadian Arctic about the location of Franklin's ships.